Distinguishing Vaccinium Species by Chemical Fingerprinting Based on NMR Spectra, Validated with Spectra Collected in Different Laboratories - Markus, Michelle A.; Ferrier, Jonathan; Luchsinger, Sarah M.; Yuk, Jimmy; Cuerrier, Alain; Balick, Michael J.; Hicks, Joshua M.; Killday, K. Brian; Kirby, Christopher W.; Berrue, Fabrice; Kerr, Russell G.; Knagge, Kevin; Gödecke, Tanja; Ramirez, Benjamin E.; Lankin, David C.; Pauli, Guido F.; Burton, Ian; Karakach, Tobias K.; Arnason, John T.; Colson, Kimberly L. (Planta Medica, 2014)
A method was developed to distinguish Vaccinium species based on leaf extracts using nuclear magnetic resonance spectroscopy. Reference spectra were measured on leaf extracts from several species, including lowbush blueberry (Vaccinium angustifolium), oval leaf huckleberry (Vaccinium ovalifolium), and cranberry (Vaccinium macrocarpon). Using principal component analysis, these leaf extracts were resolved in the scores plot. Analysis of variance statistical tests demonstrated that the three groups differ significantly on PC2, establishing that the three species can be distinguished by nuclear magnetic resonance. Soft independent modeling of class analogies models for each species also showed discrimination between species. To demonstrate the robustness of nuclear magnetic resonance spectroscopy for botanical identification, spectra of a sample of lowbush blueberry leaf extract were measured at five different sites, with different field strengths (600 versus 700 MHz), different probe types (cryogenic versus room temperature probes), different sample diameters (1.7 mm versus 5 mm), and different consoles (Avance I versus Avance III). Each laboratory independently demonstrated the linearity of their NMR measurements by acquiring a standard curve for chlorogenic acid (R2 = 0.9782 to 0.9998). Spectra acquired on different spectrometers at different sites classifed into the expected group for the Vaccinium spp., confirming the utility of the method to distinguish Vaccinium species and demonstrating nuclear magnetic resonance fingerprinting for material validation of a natural health product.
Keywords: NMR fingerprinting; Vaccinium spp.; Ericaceae; nontargeted screening; multilab study; metabolomics